Evolution of water technology from a structural perspective - Gan, Lin; Wei, Yongping; Wu, Shuanglei (Frontiers in Environmental Science, 2024)
Rivers are cradles of human civilisations and continual innovations in water technologies are the key to sustainable human development. Yet, few study has been conducted on the interactive dynamics among different technologies, compromising our capacity to efficiently manage and direct technology transition. This paper developed a framework that conceptualized water technology as a complex adaptive system containing three sub-systems: water demand, water supply, and water management. The interactions of these sub-systems are measured using three network-based metrics: intensity, brokerage, and efficiency. Patents registered in the World Intellectual Property Organization from 1863 to 2020 were used as the data source. A total of 40,304 from 44 countries were involved, with 40% of them belonging to the water management sub-system, followed by water supply (35%), and water demand (25%). Technologies development in the three sub-systems presented a linear growth rate and tended to be homogeneous in the past 160 years, focusing on water treatment, hydroelectric power, hydraulic engineering and water monitoring. Water-demand sub-system was identified as the structural "bottleneck" with the highest brokerage value, which was considered crucial for knowledge transfer between the other two sub-systems. These characteristics of the water technology system including slow development, skewed spatial coverage, categorical homogeneity, and structural imbalances could not address the increasing global water threats to human society.